Formulation and development of industry feasible proniosomal transdermal drug delivery system of granisetron hydrochloride (Asian Journal of Pharmaceutics (AJP), 2015)
Proniosomes gel is semisolid liquid crystal products of nonionic surfactants, which converted into niosomes uponhydration. A proniosome based transdermal drug delivery system of granisetron hydrochloride (GRA HCL) developed by coacervation phase separation method. Formulation optimized by use of 32 full factorial design. Span 60 and cholesterol selected as independent variables, while entrapment efficiency (EE) and flux selected as dependent variables. Proniosomes evaluated for EE, in vitro permeation study, stability study, microscopial examination by photomicroscopy, scanning electron microscopy, particle size analysis. F5 batch containing 90 mg span 60, and 10 mg cholesterol show maximum entrapment (66.57 ± 0.20%) and flux (7.94 ± 0390 μg/cm2/h). Comparative in vitro drug release study of plain drug solution and drug in proniosomal gel form was carried out for 48 h on guinea pig skin. It was found that cumulative release and flux of proniosomal gel was nearly two times more than drug solution containing same drug concentration.The study demonstrated the effectiveness of proniosomal transdermal patch containing GRA HCL for effective management of chemotherapy induced nausea and vomiting.Key words: Factorial design, industry feasible, niosomes, proniosomes, stability, transdermal drug delivery